Applying artificial intelligence in cyber security analytics and cyber threat detection - Mahajan, Shilpa; Khurana, Mehak; Estrela, Vania Vieira (John Wiley & Sons, Inc., 2024)
"Today, it's impossible to deploy effective cybersecurity technology without relying heavily on machine learning. With machine learning, cybersecurity systems can be analyzed using patterns and learn from them to help prevent similar attacks and respond to changing behavior. It can help cybersecurity teams to be more proactive in preventing threats and responding to active attacks in real time. In short, machine learning can make cybersecurity simpler, more proactive, less expensive, and far more effective. AI cybersecurity, with the support of machine learning, is set to be a powerful tool in the looming future. As with other industries, human interaction has long been essential and irreplaceable in security. While cybersecurity currently relies heavily on human input, we are gradually seeing technology become better at specific tasks than we are"-- Provided by publisher.
Keywords: Computer security -- Technological innovations.; Artificial intelligence.; Computer networks -- Security measures.; Computer crimes -- Prevention.; elektronické knihy; electronic books